A dramatic trilogy «1945» by A. I. Solzhenitsyn as a genre triad - Goncharova-Grabovskaya, Svetlana Y. (Journal of the Belarusian State University. Philology, 2019)
A dramatic trilogy «1945» by A. I. Solzhenitsyn is presented as a genre triad (comedy, tragedy, drama), its specifics is disclosed. As we note, its first part «Victory Celebrations» (1951) is a comedy, but there are no any external comical features. Its refractions are placed in the subtext of the play (the victors are the hostages of Stalin’s politics, they celebrate the Pyrrhic victory). Solzhenitsyn’s laughter is ironical and unkind, it is displayed in the title itself, which includes skepticism and irony. The second part, «Prisoners» (1953), is a tragedy not only at the discourse level, but by genre. Its character is a winner in its spirit though he is sentenced to the death. The third part, «The Love-Girl and the Innocent» (1954), is a drama of the people who got to Gulag, the place where they find new meaning of truth, lie, justice. We emphasize the phenomenon of Solzhenitsyn as a playwright: the disproportion of the literary time and space which is characteristic for his plays (the events fit to the years, days, but the literary time includes the panorama of history) lends the epic features to the trilogy.